2015
DOI: 10.11648/j.ijbmr.20150304.11
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Histological Study of the Effect of Lead on Hepatocytes of Albino Rats

Abstract: Lead is found at low levels in Earth's crust, mainly as lead sulfide. Lead is toxic for virtually all organs of the body and has significant debilitating effects on the nervous, renal, hepatic and hematopoietic systems. The liver is considered as one of the target organs affected by lead toxicity owing to its site of storage after exposure. Also, the liver is being one of the major organs involved in the biotransformation and detoxification of toxic substances. Absorbed lead is stored in soft tissues mainly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In this study, the male rats were treated with Pb, the histological sections demonstrated changes in the liver tissue such as congestion, necrosis, central vein dilation, liver vacuolation, inflammatory cell infiltration, and hyperplasia [12].…”
Section: Discussionmentioning
confidence: 76%
“…In this study, the male rats were treated with Pb, the histological sections demonstrated changes in the liver tissue such as congestion, necrosis, central vein dilation, liver vacuolation, inflammatory cell infiltration, and hyperplasia [12].…”
Section: Discussionmentioning
confidence: 76%
“…It was found that the main toxic effect of lead in the mature liver was the alteration of membranes of the endothelium, red blood cells and hepatocytes [12]. The typical morphological changes in the liver in experiments with short period lead treatment were the hypertrophy of hepatocytes, vacuolization of cytoplasm, portal space and central vein dilatation, congested central veins, narrowing or even obliteration of sinusoids and the activation of macrophages and lymphocytes with further mononuclear cellular infiltration of the portal tracts [11,26]. The degree of the liver alteration was dependent on the duration of lead exposure [11].…”
mentioning
confidence: 99%
“…The typical morphological changes in the liver in experiments with short period lead treatment were the hypertrophy of hepatocytes, vacuolization of cytoplasm, portal space and central vein dilatation, congested central veins, narrowing or even obliteration of sinusoids and the activation of macrophages and lymphocytes with further mononuclear cellular infiltration of the portal tracts [11,26]. The degree of the liver alteration was dependent on the duration of lead exposure [11]. The submicroscopic changes of hepatocytes included the alteration of mitochondria, nuclei and membranes of hepatocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation